Caracterização da população portadora de tuberculose do município de Américo Brasiliense/SP, no período de 1992 a 2002 - Severo, N. P F [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (My University, 2005)
Tuberculosis (TB) is a serious public health problem all over the world, which was recognized by the WHO in 1993 as a global emergency because of its very high incidence in the 22 countries that concentrate 80% of TB cases. One of these countries is Brazil, where TB occurrences are well-documented in major cities, but little is known of its spread in rural areas and small towns. Therefore, an epidemiological study was done on medical records of TB sufferers in the rural district and small town of Américo Brasiliense, São Paulo state, from 1992 to 2002, with the aim of improving TB prevention and treatment. The results showed that the incidence of TB peaked in the years of intense migration of rural workers, largely cane-cutters. Among these, the disease attacks mainly the men, in their productive years (20 to 40 years old). The predominant clinical form observed was pulmonary tuberculosis. The treatment abandonment rate was less than 1.8%, while the cure rate was around 90%. The disease detection rate by examination of sputum for acid-fast bacilli was around 60%.

A tuberculose é um grave problema de Saúde Pública em todo o mundo, sendo desde 1993 considerada pela OMS uma emergência global. O Brasil ocupa a 13ª posição no ranking mundial em incidência de tuberculose. Ocorrências de tuberculose nas grandes cidades brasileiras são bem conhecidas e estudadas. Entretanto, pouco se sabe sobre a problemática da tuberculose nas pequenas cidades. Neste sentido, este trabalho visou obter as características epidemiológicas da população portadora de tuberculose do município de Américo Brasiliense, SP, no período de 1992 a 2002. Os resultados mostraram que a incidência de tuberculose nesta cidade teve picos coincidentes com os anos de intensa migração de mão de obra, sobretudo para o corte da cana de açúcar e que a tuberculose acomete principalmente os trabalhadores rurais do sexo masculino, na idade produtiva dos 20 aos 40 anos. Foi verificado também que a tuberculose pulmonar é a principal forma clínica e que os índices de abandono de tratamento e de cura, foram respectivamente de 1,8% e aproximadamente, de 90%. O índice de detecção da doença pela baciloscopia foi de cerca de 60% . Palavras-chave: Tuberculose, população, epidemiologia, trabalhador rural.
Characterization of tuberculosis patients of América Brasiliense's city on 1992 to 2002
Keywords: Epidemiology; Population; Rural workers; Tuberculosis; acid fast bacterium; Brazil; human; incidence; lung tuberculosis; medical record; migration; rural population; sputum analysis